The Art of Symbolic Resistance Uyghur Identities and Uyghur-Han Relations in Contemporary Xinjiang - Smith Finley, Joanne N. (Brill, 2013)
Against the background of the Ürümchi riots (July 2009), this book provides a longitudinal study of contemporary Uyghur identities and Uyghur-Han relations. Previous studies considered China's Uyghurs from the perspective of the majority Han (state or people). Conversely, The Art of Symbolic Resistance considers Uyghur identities from a local perspective, based on interviews conducted with group members over nearly twenty years. Smith Finley rejects assertions that the Uyghur ethnic group is a 'creation of the Chinese state', suggesting that contemporary Uyghur identities involve a complex interplay between long-standing intra-group socio-cultural commonalities and a more recently evolved sense of common enmity towards the Han. This book advances the discipline in three senses: from a focus on sporadic violent opposition to one on everyday symbolic resistance; from state to 'local' representations; and from a conceptualisation of Uyghurs as 'victim' to one of 'creative agent'.